Bilioptysis – Two Case Reports of Broncho Biliary Fistula - Thangavelu, Pugazhendhi; Munirathinam, Manoj; Kini, Ratnakar (Journal of Digestive Endoscopy, 2017)
Bronchobiliary fistula (BBF) is a tract between the biliary system and bronchial tree with the presence of bile in the bronchus and the sputum. They are rare but serious complications. In most cases, they are caused by hepatic or subphrenic abscesses, resulting from different conditions. Pulmonary symptoms dominate the clinical picture, and the main manifestations are chronic irritant cough, production of greenish sputum, bronchopneumonia, and dyspnea. The diagnosis of BBF can be confirmed by imaging procedures such as biliary scintigraphy with hepatobiliary iminodiacetic acid, percutaneous transhepatic cholangiography, or endoscopic retrograde cholangiopancreatography. Bronchoscopy can demonstrate the presence of bile in the bronchial tree and may delineate the site of fistula. The treatment strategy for patients with BBF and biliary tract obstruction is the reestablishment of bile drainage, which allows the fistula to heal by reducing intrabiliary pressure. We present two cases of biliary-bronchial fistula, one related to hepatic abscess and the other due to percutaneous transhepatic biliary drainage for common bile duct obstruction secondary to inoperable hilar cholangiocarcinoma.
Keywords: Bilioptysis; bronchobiliary fistula; hepatobiliary iminodiacetic acid scan